Cochrane Database of Systematic Reviews 2009
DOI: 10.1002/14651858.cd006884.pub2
|View full text |Cite
|
Sign up to set email alerts
|

Methotrexate for maintenance of remission in Crohn's disease

Abstract: Intramuscular methotrexate at a dose of 15 mg/week is safe and effective for maintenance of remission in Crohn's disease. Oral methotrexate (12.5 to 15 mg/week) does not appear to be effective for maintenance of remission in Crohn's disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
39
0
7

Year Published

2010
2010
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(47 citation statements)
references
References 17 publications
1
39
0
7
Order By: Relevance
“…The success of methotrexate in induction and maintenance of remission in Crohn's disease has sparked interest in its potential use in ulcerative colitis. [112][113][114][115] A recent Cochrane review concluded that induction of remission with methotrexate is not supported by currently published literature, predominantly owing to insufficient data. 116 Retrospective data evaluating methotrexate maintenance therapy has yielded conflicting results.…”
Section: Methotrexatementioning
confidence: 99%
“…The success of methotrexate in induction and maintenance of remission in Crohn's disease has sparked interest in its potential use in ulcerative colitis. [112][113][114][115] A recent Cochrane review concluded that induction of remission with methotrexate is not supported by currently published literature, predominantly owing to insufficient data. 116 Retrospective data evaluating methotrexate maintenance therapy has yielded conflicting results.…”
Section: Methotrexatementioning
confidence: 99%
“…14 However, all of them recovered after proper treatment after MTX withdrawl, which is consistent with previous results that such adverse events were generally mild in nature. 15 In conclusion, MTX at a dose of 15 mg/week or 20 mg/week i.m. is safe and effective and it may serve as an alternative immunosuppressive treatment for patients who are intolerant of thiopurine.…”
Section: Discussionmentioning
confidence: 85%
“…MTX at 25 mg weekly for induction of remission and 15 mg/week for maintenance of remission has been demonstrated. 14,15 However, neither of these Cochrane reviews included Asian studies because of the scant data. Feagan et al showed a 65% remission rate at week 40 with i.m.…”
Section: Discussionmentioning
confidence: 99%
“…Current conventional options for pharmacological maintenance of medically achieved CD remission, for which there is a strong evidence base, include thiopurines (e.g. azathioprine and mercaptopurine) [2], methotrexate [3] and anti-TNF-α (infliximab and adalimumab in the UK, and in some other countries also certolizumab) [4]. In contrast, in some patients with ileal CD of limited extent, surgery may be the best option for remission maintenance, but to date there are no controlled data comparing long-term outcome in such patients treated with resection or, for example, azathioprine.…”
Section: Aims Of Options For and Limitations Of Maintenance Therapy mentioning
confidence: 99%